Fire simulation of a scaled Mass Rapid Transit (MRT) tunnel / Razieh Khaksari Haddad ... (et al.) - Haddad, Razieh Khaksari; Reda, Eslam; Rasani, Mohammad Rasi; Malok Zedan, Cristian; Harun, Zambri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The risk of serious accidents increases with the number of road tunnels and their users. Considering the importance of protecting passenger's safety and health in underground tunnels, analysis of the fire flow by the computational fluid dynamics (CFD) simulation is a necessity. The most common ventilation system is the longitudinal ventilation system used in underground tunnels in Malaysia. A major parameter for the designing of this kind of ventilation system is to calculate the "the critical velocity of ventilation" for the system. The value of the critical ventilation velocity is the minimum velocity which can eliminate the backlayering flow, and drive it downstream. This paper carries out a CFD simulation of an unexpected fire occurring in a one-way MRT tunnel with a 2.266 kW fire. This article focuses on the effect of various forced ventilation velocities on the temperature distribution and the stratification of the pollutant to estimate the critical velocity. The results indicate that an increase in the inlet velocity causes the backlayering length decreases. It can also be shown that the average temperature decreases with increasing longitudinal velocity due to a large amount of entrained fresh air. The results on backlayering and critical ventilation velocity could be utilized by firefighting services designers in preparing the design of such services.